Answer:
4
Step-by-step explanation:
From the graph, the roots of the polynomial are -2, 1, and 1.
Therefore, the polynomial P(x) is defined below:
![P(x)=(x+2)(x-1)(x-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/8bdt2girs62ei4c2ln84jyxeqgd435n9jt.png)
When P(x) is divided by x+1, the remainder will be the value of x when x+1=0
When x+1=0
![x=-1](https://img.qammunity.org/2023/formulas/mathematics/college/di7tgv2dgty5ck1t8uxuokptc8rphbkzsi.png)
Therefore:
![\begin{gathered} P(-1)=(-1+2)(-1-1)(-1-1) \\ =1*-2*-2 \\ =4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/tdgdxssr4zjbuop4i9ir5p8jgs9pe9nia0.png)
The remainder when P (x) is divided by (x + 1) is 4.